2015
DOI: 10.1080/19476337.2015.1054885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed, muscle type, and frozen storage on physico-chemical characteristics of lamb meat and its relationship with tenderness

Abstract: Effects of breed, muscle type, and frozen storage on physico-chemical characteristics of lamb meat and its relationship with tenderness, CyTA -Journal of Food, 14:1, 109-116, DOI: 10.1080/19476337.2015 To link to this article: https://doi.org/10. 1080/19476337.2015 The effects of breed, muscle types, and frozen storage time on the physico-chemical characteristics of the two most important China breeds were considered. Twenty-four lambs of Bashbay and Xinjiang Merino sheep of 7-9 months old were slaughtered, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 46 publications
11
28
0
Order By: Relevance
“…Ablikim et al. () demonstrated that changes (both increase and decrease) in the pH of lamb meat during freezer storage were correlated with the animal's breed and the analyzed muscle.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Ablikim et al. () demonstrated that changes (both increase and decrease) in the pH of lamb meat during freezer storage were correlated with the animal's breed and the analyzed muscle.…”
Section: Resultsmentioning
confidence: 89%
“…Ablikim et al. () noted high variation in the content of dry matter and fat in samples of lamb meat (collected from three different muscles) stored for 1, 7, 15 and 30 days (−18°C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, the results of research studies that investigated the influence of freezing time on the pH of meat are inconclusive. For example, Ablikim et al (2016) demonstrated that changes in the pH of lamb meat during freezer storage (30 days, -18 °C) were correlated with animal breed and type of muscle.…”
Section: Resultsmentioning
confidence: 99%